A vocal basis for the affective character of musical mode in melody - Bowling, Daniel (Frontiers in Psychology, 2013)
Why does major music sound happy and minor music sound sad? The idea that different musical modes are best suited to the expression of different emotions has been prescribed by composers, music theorists, and natural philosophers for millennia. However, the reason we associate musical modes with emotions remains a matter of debate. On one side there is considerable evidence that mode-emotion associations arise through exposure to the conventions of a particular musical culture, suggesting a basis in lifetime learning. On the other, cross-cultural comparisons suggest that the particular associations we make are supported by musical similarities to the prosodic characteristics of the voice in different affective states, indicating a basis in the biology of emotional expression. Here, I review developmental and cross-cultural studies on the affective character of musical modes, concluding that while learning clearly plays a role, the emotional associations we make are (1) not arbitrary, and (2) best understood by also taking into account the physical characteristics and biological purposes of vocalization.